Patients' perceptions and factors affecting dialysis modality decisions - Friberg, Ingrid O. (2019)
Background: Home-based dialysis, including peritoneal dialysis (PD) and home hemodialysis (HHD), has been shown to be associated with lower costs and higher health-related quality of life than in-center HD. However, factors influencing the choice of dialysis modality, including gender, are still not well understood. Methods: A questionnaire was sent out to all dialysis patients in the western region of Sweden in order to investigate factors affecting choice of dialysis modality. Logistic regression was used to analyze the data. Results: Patients were more likely to have home dialysis if they received predialysis information from 3 or more sources and, to a greater extent, perceived the information as comprehensive and of high quality. In addition, patients had a lower likelihood of receiving home dialysis with increasing age and if they lived closer to a dialysis center. Men had in comparison with women a greater likelihood of receiving home dialysis if they lived with a spouse. In-center dialysis patients more often believed that the social interaction and support provided through in-center HD treatment influenced the choice of dialysis modality. Conclusion: This study highlights the need for increased awareness of various factors that influence the choice of dialysis modality and the importance of giving repeated, comprehensive, high-quality information to dialysis and predialysis patients and their relatives. Information and support must be adapted to the needs of individual patients and their relatives if the intention is to improve patients' well-being and the proportion of patients using home dialysis.